Automated Concept of Potato Sizing Equipment. (2015) - Edu, Filip Vladimir; Cazangiu, Diana; Csatlos, Carol
Abstract: The paper presents an automated concept of a potato sizing equipment. The technological flow is represented by dimension charts done in the software CATIA v5 r18. The classical technological flows of potato sizing are rigid systems, but modern systems are flexible and have modular construction. Modular construction has the advantage that when a component of the equipment breaks out, it can be moved away and thus not affecting the entire equipment. The role of automation is illustrated by the designing of an original potato sizing machine, based on the real geometrical quotation.